Middle-Late Miocene Tidal-related Deposits of the Binio Formation: the Sedimentary and Stratigraphic Records during Inversion of the Central Sumatra Basin, Indonesia (Rudarsko-geološko-naftni zbornik, 2025)
The distribution of tidal-related deposits can be controlled by structural growth. This structural growth can be reflected, for example, by inversion structures in a back-arc basin. An example of such a structure is found in the Central Sumatra Basin (CSB), Indonesia. However, there are limited detailed studies using 3D seismic, well, and core data to understand how structural growth controls sedimentary processes and tidal deposit distribution in the CSB. This study utilizes these data to investigate the sedimentary processes and distribution of the Middle-Late Miocene Binio Formation, which was deposited during basin inversion. Sedimentological analysis, sequence stratigraphy, and Root Mean Square (RMS) attribute analysis were conducted on these data. Sedimentological analysis of the core data revealed the presence of tidal sand body and open marine facies. Furthermore, by integrating gamma-ray log and laboratory data, parasequences bounded by flooding surfaces were identified. The stratigraphic framework showed that the tidal sand body occurred before and after maximum flooding surfaces, forming transgressive and regressive tidal sand ridges. RMS attribute analysis indicated a consistent NW-trending orientation of these ridges near the flooding surfaces, implying the influence of a NW-trending tidal current, and a NE-trending paleo-shoreline near the Barisan Mountain, which affected sedimentary distribution and paleogeography during the Middle-Late Miocene. Additionally, the investigation of the relationship between ridges and reverse faults revealed that the ridges were likely controlled by tectonic activity. This study highlights that the temporal and spatial evolution of the ridges in the CSB was driven by the interaction between sediment supply and accommodation space, likely influenced by reverse fault growth and sea-level variations.